Sulforaphane acutely activates multiple starvation response pathways - Plafker, Kendra S.; Georgescu, Constantin; Pezant, Nathan; Pranay, Atul; Plafker, Scott M. (Frontiers in Nutrition, 2025)
Sulforaphane (SFN) is an isothiocyanate derived from cruciferous vegetables that has demonstrated anti-cancer, anti-microbial and anti-oxidant properties. SFN ameliorates various disease models in rodents (e.g., cancer, diabetes, seizures) that are likewise mitigated by dietary restrictions leading us to test the hypothesis that this compound elicits cellular responses consistent with being a fasting/caloric restriction mimetic. Using immortalized human retinal pigment epithelial cells, we report that SFN impacted multiple nutrient-sensing pathways consistent with a fasted state. SFN treatment (i) increased mitochondrial mass and resistance to oxidative stress, (ii) acutely suppressed markers of mTORC1/2 activity via inhibition of insulin signaling, (iii) upregulated autophagy and further amplified autophagic flux induced by rapamycin or nutrient deprivation while concomitantly promoting lysosomal biogenesis, and (iv) acutely decreased glucose uptake and lactate secretion followed by an adaptive rebound that coincided with suppressed protein levels of thioredoxin-interacting protein (TXNIP) due to early transcriptional down-regulation. This early suppression of TXNIP mRNA expression could be overcome with exogenous glucosamine consistent with SFN inhibiting glutamine F6P amidotransferase, the rate limiting enzyme of the hexosamine biosynthetic pathway. SFN also altered levels of multiple glycolytic and tricarboxylic acid (TCA) cycle intermediates while reducing the inhibitory phosphorylation on pyruvate dehydrogenase, indicative of an adaptive cellular starvation response directing pyruvate into acetyl coenzyme A for uptake by the TCA cycle. RNA-seq of cells treated for 4 h with SFN confirmed the activation of signature starvation-responsive transcriptional programs. Collectively, these data support that the fasting-mimetic properties of SFN could underlie both the therapeutic efficacy and potential toxicity of this phytochemical.